Developing Traceability Systems for Effective Circular Economy of Plastic: A Systematic Review and Meta-Analysis - Gazeau, Benjamin; Zaman, Atiq; Minunno, Roberto; Shaikh, Faiz (2024)
Annually, the global plastic waste generation adds up to over 353 million tonnes, which is associated with substantial environmental and societal issues, such as microplastic pollution and landfill management. Despite many attempts to integrate sustainable circular economy strategies into the plastic industry, several challenges have resulted in material loss and poor-quality recycled products. To address these challenges, this study proposes a material traceability system to overcome the issue of flawed recycling of plastic. The authors employed a systematic literature review and meta-analysis to summarise the current state of traceability in the plastic recycling industry. The results revealed that blockchain technology is the most promising framework amongst various traceability systems; however, its implementation is hindered for three reasons. First, future systems must prioritise interoperability to ensure seamless integration; second, standardisation is imperative for effective traceability; and third, implementing digital and physical traceability is essential to maximise the value of materials by enabling improved material identification and enhancing sorting efficiency. Further, it emerged that integrating quality control into traceability solutions is essential for improved recycled content in plastic products. By shedding light on these insights, this study contributes to developing traceability systems in the plastic recycling industry, guiding policymakers, industry practitioners, and researchers alike. Ultimately, the implementation of effective traceability mechanisms has the potential to drive plastic circularity by improving material identification, sorting practices, and overall transparency within the industry.